Evidence-Based Optimization of Classroom Teaching Units Using 3D Printers for Designing Models-From the 2D Picture to the 3D Flower Model - Marcel Bonorden; Jutta Papenbrock (MDPI AG, 2022)
The implementation of digital tools into science education is a major demand of various stakeholders, such as teachers, schools and ministries of education. However, teaching innovations and the introduction of new competences need to be carefully tested and optimized for successful and sustainable application and learning success. Our aim was to develop and establish an easily adaptable teaching unit comprising the aspects of 3D printing from computer-aided modeling to slicing, printing and post-processing, which is linked to curricular learning content. The original teaching concept developed with a small group of students has been adapted to the conditions in large groups and full-size 9th grade school classes. With an increased sample size, it was now possible to investigate and analyze the teaching approach with respect to student's motivation, learning success as well as the quality and acceptance of the teaching-learning arrangement for designing and 3D printing flower models. The goal of the study was to further optimize the existing teaching tool based on the evaluation of the student experience. While the exploration of this teaching approach ties into the current discourse of innovative biology teaching, the efficacy is evidenced by results that indicate a positive impact on student's motivation and a high learning success regarding computer-aided modeling and 3D printing. As a result, the teaching-revised concept reported in this article is based on the students' evaluation and can be provided as well-tested teaching material for schools.